THE INFLUENCE OF GUIDED READING TECHNIQUE TOWARD STUDENTS' READING COMPREHENSION - Eva Saptarina (Language and Education Journal, 2017)
Guided reading is a technique that a teacher can use to help students become great readers. Reading is the most dominant skill in learning because the ability to read is not only a performance to pronounce the passage but also an understanding the message from a passage or text. Therefore, the main purpose of this study was to prove whether or not the students who were taught reading by using guided reading technique had significantly different achievement than that of those who were not. In conducting this study a quasi-experimental method was used. The sample was taken by using purposive sampling method. The writer used the written test in the form of multiple choice. In this study, content validity was used. The t-test was used to analyze the data. Based on the independent sample t-test, it was found that the mean difference between experimental and control groups was 12.353 at the significant level p<0.05 in two-tailed testing with df= 68, t-obtained was 3.811, and the critical value of t-table was 1.9955. Since t-obtained (3.811) was higher than t-table (1.9955) and p-value(0.000) was less than α-value (0.05), it showed that null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It meant that there was a significant difference in students' reading comprehension between the students who were taught using guided reading technique and that of those who were not